2017
DOI: 10.1038/s41598-017-18178-0
|View full text |Cite
|
Sign up to set email alerts
|

Econazole nitrate inhibits PI3K activity and promotes apoptosis in lung cancer cells

Abstract: The phosphatidylinositol-3-kinase (PI3K)/AKT signaling pathway plays a pivotal role in many cellular processes, including the proliferation, survival and differentiation of lung cancer cells. Thus, PI3K is a promising therapeutic target for lung cancer treatment. In this study, we applied free and open-source protein-ligand docking software, screened 3167 FDA-approved small molecules, and identified putative PI3Kα inhibitors. Among them, econazole nitrate, an antifungal agent, exhibited the highest activity in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 51 publications
(51 reference statements)
2
16
0
Order By: Relevance
“…Remarkably, the π-Stacking interaction is constructed with TYR 867. So, we thought that TIC might be a potent inhibitor of PI3K due to the primary pharmacological structure of TIC is an imidazole ring similar to the structure of Econazole, as imidazole antifungal that recently docked PI3K by −7.3 kcal/mol that diminished P-AKT and Bcl2 protein levels [ 34 ]. In our in-silico study, the molecular docking approach was used to study the molecular affinity of TIC with autophagic related proteins ATG4B and PI3Kα, γ isoforms compared to CQ and DOX.…”
Section: Resultsmentioning
confidence: 99%
“…Remarkably, the π-Stacking interaction is constructed with TYR 867. So, we thought that TIC might be a potent inhibitor of PI3K due to the primary pharmacological structure of TIC is an imidazole ring similar to the structure of Econazole, as imidazole antifungal that recently docked PI3K by −7.3 kcal/mol that diminished P-AKT and Bcl2 protein levels [ 34 ]. In our in-silico study, the molecular docking approach was used to study the molecular affinity of TIC with autophagic related proteins ATG4B and PI3Kα, γ isoforms compared to CQ and DOX.…”
Section: Resultsmentioning
confidence: 99%
“…In another study, econazole-treated NS1 myeloma cell lines showed reduced proliferation, viability, survival, and dose-dependent changes in DNA synthesis (Denyer et al, 1985). Imidazole antifungal drugs are known to inhibit the proliferation and invasion of breast cancer cells (Bae et al, 2018) and suppress phosphoinositide 3-kinase (PI3K) activity and cause apoptosis of lung cancer cells (Dong et al, 2017). In PC3 human prostate cancer cells, econazole increased the intercellular concentration of Ca 2+ by stimulating Ca 2+ influx into cells and Ca 2+ release from the endoplasmic reticulum via a phospholipase C (PLC)-independent mechanism and inhibited cell proliferation in a dose-dependent manner (Huang et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…EGFR, can affect cell proliferation, invasion and angiogenesis (33). BCL-XL promotes cell survival by indirect inhibition of the activity of a pro-apoptotic pathway and is related with proliferation, survival and differentiation of lung cancer cells (34). MYC has been associated to abnormal autonomous proliferation and growth, angiogenesis and suppression of host immune responses (35) and overexpression of EPCAM has been associated epithelial tumors, specifically with an increase in migratory potential (36).…”
Section: Resultsmentioning
confidence: 99%